The cytoskeleton in spermatogenesis. Issue 2 (February 2019) - Dunleavy, Jessica E M; O'Bryan, Moira K; Stanton, Peter G; O'Donnell, Liza
Abstract : As germ cells progress through spermatogenesis, they undergo a dramatic transformation, wherein a single, diploid spermatogonial stem cell ultimately produces thousands of highly specialised, haploid spermatozoa. The cytoskeleton is an integral aspect of all eukaryotic cells. It concomitantly provides both structural support and functional pliability, performing key roles in many fundamental processes including, motility, intracellular trafficking, differentiation and cell division. Accordingly, cytoskeletal dynamics underlie many key spermatogenic processes. This review summarises the organisational and functional aspects of the four major cytoskeletal components (actin, microtubules, intermediate filaments and septins) during the various spermatogenic phases in mammals. We focus on the cytoskeletal machinery of both germ cells and Sertoli cells, and thus, highlight the critical importance of a dynamic and precisely regulated cytoskeleton for male fertility.